Microbial Sulfur Metabolism - Dahl, Christiane; Friedrich, Cornelius G. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
In nature, sulfur occurs in many different oxidation states and is one of the most versatile elements in life. It is an integral part of many important cell constituents, such as the amino acids cysteine and methionine, and many sulfur compounds serve as the basis for energy-related processes in prokaryotes. In recent years, new methods have been applied to study the biochemistry and molecular biology of reactions of the global sulfur cycle, the microorganisms involved and their physiology, metabolism and ecology. These activities have uncovered fascinating new insights for the understanding of aerobic and anaerobic sulfur metabolism.